PENINGKKATAN DIGITAL MARKETING DAN INOVASI KEMASAN PADA UMKM PANGAHA BUNGA DI KELURAHAN RONTU KOTA BIMA - Zahra Sausan; Jumyati Jumyati; Ita Purnama (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2025)
The Community Service Program on Digital Marketing and Packaging Innovation for Pangaha Bunga UMKM in Rontu Village, Bima City, aims to improve product quality and marketing through packaging innovation and digital marketing. Pangaha Bunga UMKM face challenges such as product quality that has not met modern consumer standards and conventional marketing strategies. The community service method includes needs analysis, product packaging and digital marketing training, mentoring, and evaluation. The results show that packaging innovation and digital marketing play a crucial role in expanding product marketing reach and improving product quality. Through mentoring in packaging innovation and digital marketing, Pangaha Bunga UMKM can increase product visibility, expand market share, and enhance competitiveness. Creating a Facebook account and developing an effective digital marketing strategy can help Pangaha Bunga UMKM understand and utilize the potential of packaging innovation and digital marketing optimally.